PI-103 and Quercetin Attenuate PI3K-AKT Signaling Pathway in T- Cell Lymphoma Exposed to Hydrogen Peroxide - Maurya, Akhilendra Kumar; Vinayak, Manjula (PLOS ONE, 2016)
Phosphatidylinositol 3 kinase—protein kinase B (PI3K-AKT) pathway has been considered as major drug target site due to its frequent activation in cancer. AKT regulates the activity of various targets to promote tumorigenesis and metastasis. Accumulation of reactive oxygen species (ROS) has been linked to oxidative stress and regulation of signaling pathways for metabolic adaptation of tumor microenvironment. Hydrogen peroxide (H2O2) in this context is used as ROS source for oxidative stress preconditioning. Antioxidants are commonly considered to be beneficial to reduce detrimental effects of ROS and are recommended as dietary supplements. Quercetin, a ubiquitous bioactive flavonoid is a dietary component which has attracted much of interest due to its potential health-promoting effects. Present study is aimed to analyze PI3K-AKT signaling pathway in H2O2 exposed Dalton’s lymphoma ascite (DLA) cells. Further, regulation of PI3K-AKT pathway by quercetin as well as PI-103, an inhibitor of PI3K was analyzed. Exposure of H2O2 (1mM H2O2 for 30min) to DLA cells caused ROS accumulation and resulted in increased phosphorylation of PI3K and downstream proteins PDK1 and AKT (Ser-473 and Thr-308), cell survival factors BAD and ERK1/2, as well as TNFR1. However, level of tumor suppressor PTEN was declined. Both PI-103 & quercetin suppressed the enhanced level of ROS and significantly down-regulated phosphorylation of AKT, PDK1, BAD and level of TNFR1 as well as increased the level of PTEN in H2O2 induced lymphoma cells. The overall result suggests that quercetin and PI3K inhibitor PI-103 attenuate PI3K-AKT pathway in a similar mechanism.